Increasing rewriting speed of optically driving liquid crystal display by process optimisation. Issue 1 (2nd January 2019) - Sun, Jiatong; Liu, Yang; Liu, Hao; Gong, Xiaohui; Chigrinov, Vladimir.G.
ABSTRACT: Process optimisation for increasing the response speed of optical driving liquid crystal cell was investigated in this paper. It is demonstrated that by filling LC in atmosphere condition rewriting time could be decreased to 6 s with good repeatability. Increasing the spin coating speed, the rewriting time could also decrease the azimuthal anchoring energy, but it will cause non-continuous film form of alignment layer, which causes large speed dispersion that is not good for practical use. Serial experiments show that with smaller azimuthal anchoring energy the rewriting time could be smaller. The results demonstrate that with proper fabrication process of alignment layer for liquid crystal optical rewritable e-paper, azimuthal anchoring energy could be adjusted to an optimal value, which is beneficial for achieving fastest rewriting speed and at the same time strong enough to well align LC. GRAPHICAL ABSTRACT: